PROGNOSTIC SIGNIFICANCE OF POSITRON EMISSION TOMOGRAPHY IN AUTOLOGOUS STEM CELL TRANSPLANTATION FOR NON-HODGKIN’S LYMPHOMA - V. G. Potapenko; N. B. Mikhaylova; B. I. Smirnov; I. A. Skorokhod; D. A. Chaginskaya; V. V. Ryabchikova; I. А. Samorodova; E. I. Podol’tseva; V. V. Ipatov; I. V. Boykov; V. N. Semelev; D. A. Gornostaev; et al. (Онкогематология)
Objective: evaluation and comparison of positron emission tomography (PET) prognostic value with other predictors of effectiveness in patients with non-Hodgkin’s lymphoma (NHL) receiving high-dose chemotherapy with autologous hematopoietic stem cell transplantation (AHSCT).Materials and methods. The retrospective data on 49 consecutive patients with NHL  receiving high-dose chemotherapy with АHSCT was               analyzed. The median age was 36.2 (7–60)  years. Median follow-up is currently 24 (1–82)  months. Prognostic factors analyzed included sex, response to the initial chemotherapy, time to relapse, second-line chemotherapy regimen type, B-symptoms on relapse, serum lactate dehydrogenase and albumin levels, response assessed by computer tomography (CT), number of chemotherapy lines, condition regimen, PET-scan results before (PET1, n = 49) and after (PET2, n = 39) AHSCT.Results. Two-year overall and event-free survivals were 74.4 and 79.1 %, respectively. Patients with CT-confirmed progression prior to AH-SCT had the worse prognosis. Prognostic significance of PET-status  was shown in chemosensitive patients (partial/complete response).The overall survival in PET1-negative and PET1-positive patients were 95.4 vs 71.0 % (р = 0.019), respectively. In PET2-positive and PET2-negative patients the overall and event-free survivals were 59.8 vs 100 % (р = 0.001) and 54.4 vs 94.4 % (р = 0.02), respectively.     In combined analysis of PET1 and PET2 statuses prognostic significance of PET2 prevailed over PET1 results significance. The multivariate analysis confirmed only PET1 significance for survival prediction.   Conclusion. Chemosensitivity of the tumor, assessed by CT, is the most important prognostic factor. In chemosensitive patients achievement PET1 or PET2 negativity means better prognosis. The patients with PET positivity prior and after AHSCT have the worst prognosis.